On the Information Problem of DNA in the Denaturation Process - Ha My, Vi Thi; Huong, Vu Thuy; Anh, Chu Thuy; Thao, To Thi; Thanh, Ngo Van; Viet, Nguyen Ai (Communications in Physics, 2011)
The information problem of DNA in the denaturation process was studied by the relationship between entropy and information. Using the previous PB’s (Peyrard and Bishop) numerical results obtained from their microscopic arharmonic model of DNA, we propose a new effective simple model to calculate DNA information. A shape change of information at the denaturation phase transition point was found and discussed.